Pengelolaan Lahan Alternatif Untuk Konservasi Sumberdaya Air Di Das Batugantung, Kota Ambon - Agustinus Jacob (Agrologia, 2013)
Land degradation on the upper stream area in Ambon island has reduced the availability of fresh water for the peoples. An available fresh water supports only 19.14% of total population.  This research was carried out to solve the problem of water resources shortage in Ambon city which is sourced from Batugantung.  The objectives of this research were to evaluate the impact of land use changes on the income, hydrological characteristics, erosion and sedimentation in Batugantung watershed. The result of this research showed that the increasing density and coverage of vegetation can increase the sustainability of land and water resources.  The increasing vegetation density in agroforestry land use can imitate the role of forest in sustaining watershed hydrological function, decreasing runoff, controlling erosion as well as  increasing farmer’s  income.  By keeping  at least 30% forest in dusun land use management in  Batugantung watershed, it can sustain water yield about 75.66 liters.s-1, decrease erosion to 27.62 ton.year-1, and increase farmers income up to Rp. 15.64 million ha-1.year-1.   By applying  the result of this research to other watersheds in Ambon island, the availability water resources will be about 13.07 x 105 m3.day-1. This amount of water resources can fulfill present total requirement of fresh water for  380 thousand peoples in Ambon island which is only  6.08 x 104  m3.day-1.